2022
DOI: 10.1002/cae.22580
|View full text |Cite
|
Sign up to set email alerts
|

Data science knowledge integration: Affordances of a computational cognitive apprenticeship on student conceptual understanding

Abstract: This study implements a computational cognitive apprenticeship framework for knowledge integration of Data Science (DS) concepts delivered via computational notebooks. This study also explores students' conceptual understanding of the unsupervised Machine Learning algorithm of K‐means after being exposed to this method. The learning of DS methods and techniques has become paramount for the new generations of undergraduate engineering students. However, little is known about effective strategies to support stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…To further discuss how pedagogical elements of the scientific argumentation framework can enhance student performance, it was found that the implementation of a computational cognitive apprenticeship approach significantly impacted the students' understanding of the various types of ML models [13, 41]. As outlined in Section 4, the learning activity that encompassed this research study scaffolded the student through learning foundational knowledge, providing examples of the desired output, and prompting self‐regulated practice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To further discuss how pedagogical elements of the scientific argumentation framework can enhance student performance, it was found that the implementation of a computational cognitive apprenticeship approach significantly impacted the students' understanding of the various types of ML models [13, 41]. As outlined in Section 4, the learning activity that encompassed this research study scaffolded the student through learning foundational knowledge, providing examples of the desired output, and prompting self‐regulated practice.…”
Section: Discussionmentioning
confidence: 99%
“…While the context of the data collection is discussed further in the methodology below, it is important to draw attention to the fact that students worked through a scaffolded computational environment. The design of the learning activity drew inspiration from all four components of a computational cognitive apprenticeship model: content, method, sequencing, and sociology [8], which has successfully supported conceptual understanding in the context of data science education [41]. We briefly describe how the computational cognitive apprenticeship supported the learning process.…”
Section: Learning Design and Educational Technologymentioning
confidence: 99%
See 2 more Smart Citations